2020
DOI: 10.1108/ecam-06-2019-0336
|View full text |Cite
|
Sign up to set email alerts
|

State and determinants of inter-regional market entry practices in the Chinese construction industry: evidence from national quality award projects

Abstract: PurposeDue to the lack of industrywide data, now there is only perceptual knowledge, through survey data, that construction firms may face great challenges in geographical diversification. The article aims to provide an objective description on the state of interregional market entry practices in the Chinese construction industry. How these practices are influenced by related set of regional and industry-related factors is further studied.Design/methodology/approachDescription analysis of the practices is firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…3, 2022 extended by Just and Levinger (2021).These researchers determined that the growth in demand on the housing construction market is fueled by an increase of consumer income, the number of urban residents and better access of potential investors to capital. Wang et al (2020) analyzed regional and branch factors influencing the development of the construction industry in China. Studying the housing construction market in China, Zhai et al (2014) identified 6 factors, influencing its development, namely "constructability implementation", "social climate and attitudes", "architectural performance", "costs", "supply chain" and "preparatory stage".…”
Section: Literature Reviewmentioning
confidence: 99%
“…3, 2022 extended by Just and Levinger (2021).These researchers determined that the growth in demand on the housing construction market is fueled by an increase of consumer income, the number of urban residents and better access of potential investors to capital. Wang et al (2020) analyzed regional and branch factors influencing the development of the construction industry in China. Studying the housing construction market in China, Zhai et al (2014) identified 6 factors, influencing its development, namely "constructability implementation", "social climate and attitudes", "architectural performance", "costs", "supply chain" and "preparatory stage".…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Canadian construction market, studies have shown that the number of bids and contracts fluctuates seasonally, and the smaller the project amount, the more fellows [19]. In China, sizeable state-owned construction enterprises dominate the market competition, which is reflected in the ratio of the quantity and proportion of contracts [20]. On the contrary, in Australia [21], Portugal [22], and the United States, small and medium-sized construction enterprises have a much broader survival space.…”
Section: Competition In the Construction Marketmentioning
confidence: 99%
“…In the construction industry, where information is scarce and times are competitive, it is difficult for businesses to accurately identify and forecast competitor behavior [6]. However, the similarity between customer demand and business resources enables enterprises to address these issues [20,42]. Additionally, the construction market's overall characteristics imply the existence and influence of market commonality.…”
Section: The Theory Of Industrial Clustersmentioning
confidence: 99%
See 2 more Smart Citations